Use of sewage sludge in the production and quality of Jacaranda mimosifolia D. Don seedlings - Costa, Alice Lemos; Oliveira, Viviane da Silva; de Acis Oliveira, Nilcilene de Acis Oliveira; Gonçalves, Ana Caroline Machado; Vestena, Silvane (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
The substrate has great importance for the development of seedlings, and many materials can be used for its composition. Thus, the aim of this study was to evaluate the quality of Jacaranda mimosifolia D. Don seedlings on different substrates with sewage sludge (SS). The substrates were combined as follows: T1 (50% commercial substrate Plantmax® + 50% organic compost from horse bedding (organic compost - OC); T2 (20% SS + 80% OC); T3 (40% SS + 60% OC); T4 (60% SS + 40% OC). At 180 days after sowing, the following biometric characteristics were measured: aerial part height and root system length; stem diameter; number of leaves; fresh and dry mass of the aerial part and root; and total mass. The Dickson Quality Index (DQI) was calculated, and the content of macro and micronutrients in the root and aerial parts was quantified. The accumulation of macronutrients in the root system was in the order K>N>Mg>P>Ca>S and in the aerial part, N>Ca>K>P>Mg>S. Sulfur was less concentrated in the two vegetative structures. For the micronutrients, the accumulation in the root system was in the order Fe>Mn>Zn>Cu>B, and in the aerial part, it was Fe>Mn>Zn>B>Cu. In general, the Fe and Mn content were more concentrated in the two vegetative structures studied. The recommended substrate formulated according to our results was 60% SS + 40% OC, presenting the highest mean values of growth and biomass. Thus, the use of SS can be considered a viable substrate for the production of healthy seedlings of J. mimosifolia for planting in the field.